Fc Gamma Receptors and Their Role in Antigen Uptake, Presentation, and T Cell Activation - Junker, Fabian; Gordon, John; Qureshi, Omar (Frontiers in Immunology, 2020)
The cellular uptake, intracellular processing and presentation of foreign antigen are crucial processes for eliciting an effective adaptive host response to the majority of pathogens. The effective recognition of antigen by T cells requires that it is first processed and then presented on MHC molecules that are expressed on other cells. A critical step leading to the presentation of antigen is delivering the foreign cargo to an intracellular compartment where the antigen can be processed and loaded onto MHC molecules. Fc-gamma receptors (FcγRs) recognize IgG-coated targets, such as opsonized pathogens or immune complexes (ICs). Cross-linking leads to internalization of the cargo with associated activation of down-stream signaling cascades. FcγRs vary in their affinity for IgG and intracellular trafficking, and therefore have an opportunity to regulate antigen presentation by controlling the shuttling and processing of their cargos. In this way, they critically influence physiological and pathophysiological adaptive immune cell functions. In this review, we will cover the contribution of FcγRs to antigen-presentation with a focus on the intracellular trafficking of IgG-ICs and the pathways that support this function. We will also discuss genetic evidence linking FcγR biology to immune cell activation and autoimmune processes as exemplified by systemic lupus erythematosus (SLE).